Scutellarein Aggravated Carbon Tetrachloride-Induced Chronic Liver Injury in Gut Microbiota-Dysbiosis Mice. (15th December 2020) - Miao, Zhimin; Lai, Yong; Zhao, Yingying; Chen, Lingmin; Zhou, Jianeng; Li, Chunyan; Lan, Hai
Abstract : Scutellarein (SCU) is an herbal flavonoid, showing hepatoprotective potentials. The study was aimed to investigate whether the hepatoprotective effect of SCU is dependent on the integrity of gut microbiota. Mice received repeated intraperitoneal injections of CCl4, followed with or without SCU treatment (15, 30, and 60 mg/kg). Gut microbial community of mice was disrupted by administrating a cocktail of antibiotics (ampicillin, neomycin sulfate, metronidazole, and vancomycin) in drinking water. The results showed SCU plus antibiotics aggravated CCl4 -induced chronic liver injury, as demonstrated by liver function analysis, histological analysis, and TUNEL assay. SCU activated CYP2E1 expression and worsened CYP2E1-mediated lipid peroxidation and oxidative stress as coadministered with antibiotics. Moreover, when gut microbiota was disrupted by antibiotics, SCU activated I κ B α /NF- κ B pathway and promoted the release of subsequent proinflammatory cytokines including interleukin-6 (IL-6), interleukin-1 β (IL-1 β ), and tumor necrosis factor- α (TNF- α ). Remarkably, the 16 S rRNA sequencing demonstrated that SCU greatly decreased the relative abundance of Bifidobacterium and Lactobacillus and increased the relative abundance of Enterococcus in gut microbiota-dysbiosis mice. Spearman correlation analysis showed that Lactobacillus was positively correlated with SOD and negatively correlated with AST. Collectively, the hepatoprotective effect of SCU is reversed under antibiotics intervention, which may partly involve the activation of CYP2E1 and I κ B α /NF- κ B pathway and diminishment of Lactobacillus.